THE ROLE OF THE CITY OF KARBALA IN THE ISLAMIC WORLD - Tokhtiev Shukhrat Rustamovich (Bright Mind Publishing, 2025)
Although the holy places in Islam are considered to be Mecca and Medina, in addition to these two cities, Shias also consider Najaf, Karbala, Mashhad, Qom and other cities where Shia imams are buried as holy. Karbala, the holy city associated with the name of the second Shiite imam Husayn, is considered the main pilgrimage site of the Shiites, and the history of the city, the description of Husayn's mausoleum, has been extensively covered in the works of many historians and geographers. Due to many narratives related to Hussein's death and the deification of his personality, holy places and shrines have been created in various regions of Central Asia.
Keywords: Karbala, Husayn, Iraq, Kufa, Ninawa, Ibn Battuta, Mashadmozor, Sunbulmozor, Imam ata, Shahmozor, Shahidon.